Sb2S3 as sensitizer in semiconductor-sensitized solar cells - Kang, Aik Meng. (2011)
Dye-sensitized solar cell (DSSC) is an emerging technology with the potential to surpass first generation silicon-based solar cells and second generation thin film solar cells. To date, DSSCs have already reached efficiency of over 11 % but it has yet to display widespread commercial application in the solar panel market. This is largely due to its degradation and stability of the cell as well as the use of a liquid electrolyte which can result in leakage. Hence, this study aims to explore new materials to replace the dye and electrolyte. Antimony sulfide (Sb2S3) has been identified as a suitable candidate.